Effect of eplerenone on parathyroid hormone levels in patients with primary hyperparathyroidism: results from the Epath randomized, placebo-controlled trial - Tomaschitz, Andreas; März, Winfried; Ritz, Eberhard (Journal of hypertension, 2016)
Accumulating evidence points toward mutual interaction between parathyroid hormone (PTH) and aldosterone as potential mechanism for increasing cardiovascular risk in primary hyperparathyroidism (pHPT). The Eplerenone on parathyroid hormone levels in patients with primary hyperparathyroidism (EPATH) trial is a single-center, randomized, double-blind, parallel-group, placebo-controlled trial. The primary aim is to evaluate the effects of the mineralocorticoid receptor antagonist eplerenone on plasma intact PTH (iPTH) concentration in patients with pHPT. Secondary end points comprised surrogate parameters of cardiovascular health [24-h ambulatory SBP and DBP and echocardiographic parameters related to systolic/diastolic function as well as to cardiac dimensions]. We enrolled 110 study participants with pHPT, 25-hydroxyvitamin D at least 20 ng/ml and estimated glomerular filtration rate more than 50 ml/min per 1.73 m2. Patients were 1 : 1 randomly assigned to receive either 25 mg eplerenone once daily (up-titration after 4 weeks to 50 mg/day) or matching placebo for a treatment period of 8 weeks. The study was completed by 97 participants [mean (SD) age: 67.5 ± 9.5 years; 78.4% women). The mean treatment effect (95% confidence interval) for iPTH was 1.0 (0.9-1.1; P = 0.777) pg/ml. Mean 24-h ambulatory SBP and DBP decreased significantly [mean change (95% confidence interval) −6.3 (−9.4 to −3.3) and −3.7 (−5.7 to −1.7) mmHg, respectively; P < 0.001]. No differences were seen in any further secondary outcomes or frequency of adverse events. In pHPT, treatment with eplerenone compared with placebo had no effect on circulating iPTH levels. Eplerenone treatment was well tolerated and safe and followed by significant decrease of ambulatory blood pressure.
Gesehen am 14.02.2018